Selection of Antibiotics as Prophylaxis for Close Contacts of Patients with Meningococcal Disease in Areas with Ciprofloxacin Resistance — United States, 2024 - Isha Berry; Amy B. Rubis; Rebecca L. Howie; Shalabh Sharma; Daya Marasini; Henju Marjuki; Samuel J. Crowe; Lucy A. McNamara (2024)
Meningococcal disease, caused by the bacterium Neisseria meningitidis, is a rare but life-threatening illness that requires prompt antibiotic treatment for patients and antibiotic prophylaxis for their close contacts.Historically, N. meningitidis isolates in the United States have been largely susceptible to the antibiotics recommended for prophylaxis, including ciprofloxacin.Since 2019, however, the number of meningococcal disease cases caused by ciprofloxacin-resistant strains has increased.Antibiotic prophylaxis with ciprofloxacin in areas with ciprofloxacin resistance might result in prophylaxis failure.Health departments should preferentially consider using antibiotics other than ciprofloxacin as prophylaxis for close contacts when both of the following criteria have been met in a local catchment area during a rolling 12-month period: 1) the reporting of two or more invasive meningococcal disease cases caused by ciprofloxacin-resistant strains, and 2) ≥20% of all reported invasive meningococcal disease cases are caused by ciprofloxacin-resistant strains.Other than ciprofloxacin, alternative recommended antibiotic options include rifampin, ceftriaxone, or azithromycin.Ongoing monitoring for antibiotic resistance of meningococcal isolates through surveillance and health care providers' reporting of prophylaxis failures will guide future updates to prophylaxis considerations and recommendations.